Adrenal suppression with inhaled budesonide and fluticasone propionate given by large volume spacer to asthmatic children. Issue 9 (September 1996) - Clark, D. J.; Clark, R. A.; Lipworth, B. J.
Abstract : BACKGROUND: The aim of this study was to compare the systemic bioactivity of inhaled budesonide (B) and fluticasone propionate (F), each given by large volume spacer, on a microgram equivalent basis in asthmatic children. METHODS: Ten stable asthmatic children of mean age 11 years and forced expiratory volume in one second (FEV1) 81.6% predicted, who were receiving treatment with < or = 400 micrograms/day of inhaled corticosteroid, were studied in a placebo controlled single blind (investigator blind) randomised crossover design comparing single doses of inhaled budesonide and fluticasone propionate 400 micrograms, 800 micrograms, and 1250 micrograms. Doses were given at 20.00 hours with mouth rinsing and an overnight 12 hour urine sample was collected for estimation of free cortisol and creatinine excretion. RESULTS: The results of overnight 12 hour urinary cortisol output (nmol/12 hours) showed suppression with all doses of fluticasone propionate (as geometric means): F400 micrograms (11.99), F800 micrograms (6.49), F1250 micrograms (7.00) compared with placebo (24.43), whereas budesonide caused no suppression at any dose. A comparison of the drugs showed that there were differences at 800 micrograms and 1250 micrograms levels for urinary cortisol: B800 micrograms versus F800 micrograms (2.65-fold, 95% CI 1.26 to 5.58), B1250 micrograms versus F1250 micrograms (2.94-fold, 95% CI 1.67 to 5.15). The results for the cortisol/creatinine ratio were similar to that of urinary cortisol, with fluticasone causing suppression at all doses and with differences between the drugs at 800 micrograms and 1250 micrograms. CONCLUSIONS: Single doses of inhaled fluticasone produce greater systemic bioactivity than budesonide when given by large volume spacer on a microgram equivalent basis in asthmatic children. The systemic bioactivity of fluticasone, like budesonide, is due mainly to lung bioavailability.